The Microtubule-Modulating Drug Epothilone D Alters Dendritic Spine Morphology in a Mouse Model of Mild Traumatic Brain Injury - Chuckowree, Jyoti A.; Zhu, Zhendan; Brizuela, Mariana; Lee, Ka M.; Blizzard, Catherine A.; Dickson, Tracey C. (Frontiers in Cellular Neuroscience, 2018)
Microtubule dynamics underpin a plethora of roles involved in the intricate development, structure, function and maintenance of the central nervous system. Within the injured brain, microtubules are vulnerable to misalignment and dissolution in neurons and have been implicated in injury-induced glial responses and adaptive neuroplasticity in the aftermath of injury. Unfortunately, there is a current lack of therapeutic options for treating traumatic brain injury (TBI). Thus, using a clinically relevant model of mild TBI, lateral fluid percussion injury (FPI) in adult male Thy1-YFPH mice, we investigated the potential therapeutic effects of the brain-penetrant microtubule-stabilising agent, epothilone D. At 7 days following a single mild lateral FPI the ipsilateral hemisphere was characterised by mild astroglial activation and a stereotypical and widespread pattern of axonal damage in the internal and external capsule white matter tracts. These alterations occurred in the absence of other overt signs of trauma: there were no alterations in cortical thickness or in the number of cortical projection neurons, axons or dendrites expressing YFP. Interestingly, a single low dose of epothilone D administered immediately following FPI (and sham-operation) caused significant alterations in the dendritic spines of layer 5 cortical projection neurons, while the astroglial response and axonal pathology were unaffected. Specifically, spine length was significantly decreased, whereas the density of mushroom spines was significantly increased following epothilone D treatment. Together, these findings have implications for the use of microtubule stabilising agents in manipulating injury-induced synaptic plasticity and indicate that further study into the viability of microtubule stabilisation as a therapeutic strategy in combating TBI is warranted.